SOCIODEMOGRAPHIC AND LIFESTYLE ASPECTS VERSUS ACCESS TO TREATMENT FOR PATIENTS WITH BREAST CANCER AT A CANCER CENTER IN SÃO PAULO - Gomes Filho, José Euderaldo Costa; Rocha, Ariane Silva da; Fernandes, Gisele Aparecida; López, Rossana Verónica Mendoza; Curado, Maria Paula (Mastology, 2021)
Sociodemographic and lifestyle aspects versus access to breast cancer treatment — Single Health System (SHS) and Supplementary Health — were evaluated in a prospective cohort of patients with breast cancer. This is a cross-sectional study with 705 patients. As compared with sociodemographic characteristics, 56.5% (n=398) of the patients were seen through Supplementary Health, and for both SHS and Supplementary Health patients, there is a higher frequency of women aged above 50 years, with 62.2% (n=191) and 51% (n=203) (p=0.002); married, 48.2% (n=148) and 66.6% (n=265) (p<0.001); white, 69.4% (n=213) and 82.1% (n=325) (p<0.001); and for the level of education, 37.1% (n=114) of those with SHS had completed high school and 55.7% (n=221) (p<0.001) of those with Supplementary Health had completed college. The first mammogram occurred between the ages of 18 and 40 years, 72.5% (n=206) of the SHS participants and 88.6% (n=342) (p<0.001) for Supplementary Health; own housing for 90.6% (n=278) and 89.4% (n=354) (p<0.001); denied tobacco use, 65.5% (n=201) and 74.7% (n=296) (p=0.005); and alcohol consumption, 87.6% (n=269) and 77.2% (n=305) (p<0.001). However, there was no difference regarding previous diagnosis of breast cancer in 55.3% (n=114) and 64% (n=178) (p<0.001) and the type of care; eutrophic body mass index was 38.4% (n=118) and 42.1% (n=167) (p=0.079), respectively. Access to SHS and supplementary health care, age above 50 years, married, white, level of education, age at first mammogram, home ownership, smoking habits, and consumption of alcoholic beverages were significantly different; BMI was not different in the two groups. Therefore, the lifestyle of SHS and Supplementary Health patients was statistically different in this cohort of patients.